At War and at Home: The Consequences of US Women Combat Casualties. (April 2021) - Cohen, Dara Kay; Huff, Connor; Schub, Robert
What are the consequences of women dying in combat? We study how women fighting on the frontlines of the military affects public attitudes toward (1) military conflict and (2) women's equality. We demonstrate through a series of survey experiments that women dying in combat does not reduce public support for war. However, women's combat deaths do shape perceptions of women's equality. Women dying in combat increases support for gender equality, particularly in the public sphere of work and politics, but only among women respondents. The findings indicate that women's combat deaths do not undermine leaders' ability to garner support for war, but combat service—and indeed, combat sacrifice—alone is insufficient to yield women's "first-class citizenship" among the general US public. The results highlight how major policy changes challenging traditional conceptions of gender and war can generate positive attitudinal shifts concentrated among members of the underrepresented community.